PELATIHAN PEMBUATAN PROPELLER MOTOR KETEK MENGGUNAKAN TANUR CRUCIBLE DI KAMPUNG WANINGGAP NANGO - Kelemens A Rahangmetan; Marsujitullah Marsujitullah (Musamus University, 2021)
The propeller casting training was carried out in Waninggap Nanggo village by involving youngpeople who were given casting training in order to make a ketek motor propeller, so as to producereliable human resources (HR) in Waninggap Nanggo village who of course would provideprovisions for the use of increasingly developing technology. Purpose Casting training for homeindustries is a technology in which village youths are trained to be able to do casting whose rawmaterial comes from used aluminum which also has good mechanical properties because there isa mixture of the alloys found in the aluminum. In the ketek motor propeller casting training is atraining that uses a crucible furnace as a tool for melting aluminum, where the use of the fuelused certainly has an influence during the aluminum smelting process, so bus wood is analternative because bus wood is widely available in Merauke district bus wood has a goodcalorific value in the aluminum smelting process, which is around 3928 - 4106 kcal / kg. Thishousehold-scale casting industry training is also a new idea, because in Merauke district there isno aluminum casting industry, especially the manufacture of two blade (two-leaf) outboard motorpropellers with a size of 10 mm and managed to produce 5 propellers from the training results.implemented, therefore this training will continue to be developed so that the community inWaninggap Nanggo village because in this training the community has been able to make anoutboard / ketek motor propeller which is usually used alone or can be used as a livelihood forthe community who of course work together. with the village government of Waninggap Nanggoso that it can continue to be developed.